2012
DOI: 10.4319/lom.2012.10.807
|View full text |Cite
|
Sign up to set email alerts
|

In situ video and fluorescence analysis (VFA) of marine particles: applications to phytoplankton ecological studies.

Abstract: Phytoplankton consists of microscopic single-celled microalgae which transform, through the photosynthesis process, inorganic substances into organic biomass readily available to secondary consumers. Due to their role of primary producers, microalgae represent the basis of the marine food web. Phytoplankton is composed of a very high number of species that can be classified by functional groups (e.g., diatoms, dinoflagellates), size classes [pico-plankton (<2 µm), nano-plankton (2-20 µm), micro-plankton (> 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Basically, the stations covered all the Southern part of Brittany. Conventional sampling stations were set up using a custom-built pelagic profiler with standard sensors (CTD SBE 25, Fluorometer, Par) and specifically designed optical sensors (diffraction and video) allowing an in-situ detection and characterization of the phytoplankton community according to their morphological and fluorescence properties (Lunven et al, 2012). Over some stations, a high-resolution vertical sampling (Fine Scale Sampler-FSS, Lunven et al, 2005) was carried out when a marked vertical stratification was found.…”
Section: Observations Over the Shelfmentioning
confidence: 99%
“…Basically, the stations covered all the Southern part of Brittany. Conventional sampling stations were set up using a custom-built pelagic profiler with standard sensors (CTD SBE 25, Fluorometer, Par) and specifically designed optical sensors (diffraction and video) allowing an in-situ detection and characterization of the phytoplankton community according to their morphological and fluorescence properties (Lunven et al, 2012). Over some stations, a high-resolution vertical sampling (Fine Scale Sampler-FSS, Lunven et al, 2005) was carried out when a marked vertical stratification was found.…”
Section: Observations Over the Shelfmentioning
confidence: 99%
“…The projects focused on enhancing the understanding of the environmental factors and oceanographic phenomena that influence HAB-shellfish toxic pathways, including the role of thin layers, horizontal advection, physical forcing mechanisms such as eddies, gyres, frontal systems, bottom density fronts, upwelling and downwelling events, seasonally formed bottom density fronts and associated jets, alongshore winds and wind exchange events (e.g., Raine et al, 2010;Raine, 2014). These scientific studies were also instrumental in the development and testing new technologies and methodologies (e.g., Lunven et al, 2005Lunven et al, , 2012. New conceptual models were formulated using the observed, regional, physical forcing mechanisms and local circulation patterns, and knowledge of biophysical mechanisms that influence the distribution and cross shelf transport of HABs into aquaculture bays (Aleynik et al, 2016;Pinto et al, 2016).…”
Section: The European Union (Eu)mentioning
confidence: 99%
“…Combining the data from a nutrient sensor (e.g., Cycle Phosphate Sensor, Wetlabs; SUNA UV nitrate sensor, Satlantic) with the data from the physical, chemical, and biological sensors may help to provide a better understanding of the diel variations of various parameters (e.g., Chl a fluorescence, oxygen concentration, and calculated metabolic parameters). However, there are many other sensors for studying microorganisms and particle dynamics, such as submersible flow cytometers (Olson and Sosik 2007;Thyssen et al 2008), in situ imagery systems (Gorsky et al 2000;Lunven et al 2012), and submersible laser particle size analyzers (Agrawal and Pottsmith 2000), as well as a new generation of sensors providing information about aquatic microorganism diversity (e.g., Environmental Sampling Processor (ESP), Scholin et al 2006), which could help to increase and deepen our knowledge of marine ecology. However, most of these sensors cannot be fitted into mesocosms, because of their size, the need to clean them frequently, especially in eutrophic waters, or their high power consumptions.…”
Section: Toward Highly Autonomous Mesocosm Experimentsmentioning
confidence: 99%